Green Chemistry and Sustainability Aspects of Ionic Liquids For Bamboo Preservatives: A Didactical Content Analysis Study - Damayanti, Anita; ., Hernani; Mudzakir, Ahmad (KnE Social Sciences, 2024)
Bamboo has many benefits; it can be used as a construction material and multiple products. However, bamboo has low durability and is easily attacked by fungi and termites. One way to overcome the disadvantages of bamboo is by using environmentally friendly preservatives. Engineering done with ionic liquids can be made into a bamboo preservative that is environmentally friendly and sustainable. This feature of ionic liquids can be integrated into teaching and learning on the concepts of green chemistry and sustainability. This study aimed to produce a concept map and teaching-learning sequences from scientists’ conceptions of green chemistry and sustainability on the topic of ionic liquids. The method used in this study was qualitative content analysis. The research instrument was content analysis. The content analysis processes included literature collection, descriptive analysis, category selection, and material evaluation by didactic aspects. The results of this study are in the form of a concept map, and TLS illustrate the potential consequences of bamboo. Concept map and TLS that connects the relationship between science, technology, and engineering. The results of this study can be used as a basis for designing teaching materials and didactical sequences.Keywords: bamboo, green chemistry, sustainability, ionic liquids. Keywords: bamboo, green chemistry, sustainability, ionic liquids